Evaluating the usability and performance of e-commerce database transaction systems under real-time stress using McCall’s quality model - Siti Solehah, Othman; Noraziah, Ahmad; Roslina, Mohd Sidek (Majmaah University Center for Publishing and Translation, 2025)
E-commerce depends on database transaction systems to handle large numbers of user interactions and transactions effectively and securely. In the current literature, numerous investigations have sought to determine the usability of the systems based on McCall’s Quality Model; however, assessing system performance under real-time stress situations has not been explored much. This builds on previous research regarding adding stress testing to identify how usability, as well as performance, is impacted in heavy traffic. The present work employs an improved evaluation framework and encompasses major platforms like Shopee, Lazada, Amazon, and Flipkart and major factors, including Efficiency, Reliability, and Integrity. Implications of the study will help in designing strategies for increasing system reliability and transaction continuity and developing strategies to increase user satisfaction in present day scalable online trading environments.